PROCESSES OF DEEP OUTGASSING OF THE EARTH AS THE CAUSE OF BOTTOM CARBONATE BUILDUP FORMATION IN THE OCEAN SHELF ZONES - Omelchuk, O.; Sokur, O. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Bottom carbonate buildups of northwest of the Black Sea and western shelf of the South China Sea are considered in the article. The actual material for these researches was received when carrying out submarine works with application of underwater laboratory "Bentos-300" in the Black Sea and submersible vehicle "Sever-2" in the South China Sea. As a result of researches gas emissions from bottom depositions and carbonate builups were discovered at depths of 160-300 m. Investigation of landscape and geological setting on seabed was carried out by direct observation of gas emission fields. It was established within their limits that gas component is only one portion of fluid flow which formation is caused by deep outgassing processes of the Earth. The main portion is represented by fluid mineralized phase saturated with soluble compounds. In the marine water which is characterized by different hydrochemical parameters superimposed biochemogenic sedimentation, predominantly calcium carbonate occurs from fluid flow. Relation between buildup types, sea depth and bottom relief is defined. The most carbonate builups are confined to vertex sites of ridges. On slopes the buildups are rare and their number decreases. Cover formations of solid very strong rocks in the form of massive blocks that is 40-60 cm thick prevail at depths of 160-190 m. Distribution pattern of calcium carbonate over the section of crusts and tabular shapes points to the relation between a source of carbonates with lateral distribution of mineralized waters in near-bottom layer on the surface of sedimentary substrate. Comparative data on composition of carbonate buildups of Black and Southern Chinese Seas testify for their common features of deep hydrocarbon outgassing and tectono-geodynamic similarity between areas of their distribution. Considering the fact that within the shelf area of Vietnam, giant oil and gas fields have already been discovered and are under exploralion, prospects for discovery of similar deposits in northwest part of the Black Sea are rather reasonable. Results of studying of carbonate formations in the Black Sea can be used for forecasting and prospectings of hydrocarbonic raw material.
Keywords: deep outgassing of the Earth; carbonate buildups; hydrocarbon raw material; shelf zones of the ocean